R44_PNA_Faucon-pelerin_2021-2030-R44_PNA_Faucon-pelerin_LPO_ALS_2020 ... - Inventaire National Du Patrimoine Naturel (UMS PatriNat (OFB-CNRS-MNHN), Paris, 2022)
Évolution de la population de Faucon pèlerin dans le Grand Est dans le cadre de l'ORB ...